Testing the preservation potential of early diagenetic dolomites as geochemical archives. Issue 2 (25th October 2019) - Mueller, Mathias; Igbokwe, Onyedika A.; Walter, Benjamin; Pederson, Chelsea L.; Riechelmann, Sylvia; Richter, Detlev K.; Albert, Richard; Gerdes, Axel; Buhl, Dieter; Neuser, Rolf D.; Bertotti, Giovanni; Immenhauser, Adrian
Abstract: Early marine diagenetic dolomite is a rather thermodynamically‐stable carbonate phase and has potential to act as an archive of marine porewater properties. However, the variety of early to late diagenetic dolomite phases that can coexist within a single sample can result in extensive complexity. Here, the archive potential of early marine dolomites exposed to extreme post‐depositional processes is tested using various types of analyses, including: petrography, fluid inclusion data, stable δ 13 C and δ 18 O isotopes, 87 Sr/ 86 Sr ratios, and U‐Pb age dating of various dolomite phases. In this example, a Triassic carbonate platform was dissected and overprinted (diagenetic temperatures of 50 to 430°C) in a strike‐slip zone in Southern Spain. Eight episodes of dolomitization, a dolostone cataclasite and late stage meteoric/vadose cementation were recognized. The following processes were found to be diagenetically relevant: (i) protolith deposition and fabric‐preservation, and marine dolomitization of precursor aragonite and calcite during the Middle–Late Triassic; (ii) intermediate burial and formation of zebra saddle dolomite and precipitation of various dolomite cements in a Proto‐Atlantic opening stress regime ( T ca 250°C) during the Early–Middle Jurassic; (iii) dolomite cement precipitation during early Alpine tectonism, rapid burial to ca 15 km, and high‐grade anchizone overprint during Alpine tectonic evolution in the Early Eocene to Early Miocene; (iv) brecciation of dolostones to cataclasite during the onset of the Carboneras Fault Zone activity during the Middle Miocene; and (v) late‐stage regression and subsequent meteoric overprint. Data shown here document that, under favourable conditions, early diagenetic marine dolomites and their archive data may resist petrographic and geochemical resetting over time intervals of 10 8 or more years. Evidence for this preservation includes preserved Late Triassic seawater δ 13 CDIC values and primary fluid inclusion data. Data also indicate that oversimplified statements based on bulk data from other petrographically‐complex dolomite archives must be considered with caution.